Analysis of the Value and Advantages of Financial Literacy and Digitalization to the Individual - Afzal Sayed Munna; Rehana Khanam (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2021)
Digital literacy is the ability to analyse, evaluate and create a teaching and learning media which enables adults and youth to understand complex communication, Aufderheide (1993). Therefore, this research study has examined how digital knowledge could provide an opportunity to learn financial capability. Fintech has transformed the history of the financial sectors and places an individual at significant advantages. However, Bankers, Teachers, Information Technology (IT) professionals and university students were selected for the research study from Bangladesh and England. Interviews were conducted with management level professionals. Survey and test questionnaires were developed and randomly directed to other participants to measure their financial and ICT knowledge. The research findings have found that present financial decision making, and the growth of assets depends on an individual adult’s financial capability.